Transisi PAUD ke SD: Solusi Pendidikan Menyenangkan - Reza, Muhammad; Asbari, Masduki; Ely (AGUSPATI RESEARCH INSTITUTA, 2024)
The goal is to transition children from Early Childhood Education (PAUD) to Primary School (SD) with an approach that emphasizes character development, social skills and language. The